Factors Associated With Dysfunction of Glymphatic System in Patients With Glioma - Toh, Cheng Hong; Siow, Tiing Yee (Frontiers in Oncology, 2021)
Objectives: Rodent experiments have provided some insight into the changes of glymphatic function associated with glioma growth. The diffusion tensor image analysis along the perivascular space (DTI-ALPS) method offers an opportunity for the noninvasive investigation of the glymphatic system in patients with glioma. We aimed to investigate factors associated with glymphatic function changes in patients with glioma. Materials and Methods: A total of 201 glioma patients (mean age, 47.4 years; 116 men; 86 grade II, 52 grade III and 63 grade IV) who had preoperative diffusion-tensor imaging for calculation of the ALPS index were retrospectively included. Information collected from each patient included sex, age, tumor grade, isocitrate dehydrogenase 1 (IDH1) mutation status, peritumoral brain edema volume, tumor volume and ALPS index. Group differences in ALPS index according to sex, tumor grade, and IDH1 mutation status were assessed using analysis of covariance with age adjustment. Linear regression analyses were performed to identify factors associated with ALPS index. Results: Group comparisons revealed that ALPS index of grade II/III gliomas was significantly higher than that of grade IV gliomas (P < 0.001). ALPS index of IDH1-mutant gliomas was significantly higher than that of IDH1-wildtype gliomas (P < 0.001). On multivariable linear regression analysis, IDH1 mutation (β = 0.308; P < 0.001) and peritumoral brain edema volume (β = -0.353; P < 0.001) were the 2 independent factors associated with ALPS index. Conclusion: IDH1-wildtype gliomas and gliomas with larger peritumoral brain edema volume were associated with lower ALPS index which may reflect impaired glymphatic function.